A Tactile Virtual Reality for the Study of Active Somatosensation - Bhattacharjee, Arindam; Kajal, Diljit Singh; Patrono, Alessandra; Li Hegner, Yiwen; Zampini, Massimiliano; Schwarz, Cornelius; Braun, Christoph (Frontiers in Integrative Neuroscience, 2020)
Natural exploration of textures involves active sensing, i. e. voluntary movement of tactile sensors (e.g. human fingertips or rodent whiskers) on a target surface to acquire controlled variations of the sensory input. Despite the ecological relevance of active sensing, there is a dearth of human tactile psychophysical studies in active settings. Stimulus delivery is a considerable challenge in studies investigating active touch; however, a possible solution might be in the realm of virtual haptic environment. In addition to rigorous behavioral studies, investigation of the neuronal mechanisms of active tactile sensing in humans is highly warranted - this might require neurophysiological experiments using magnetoencephalography (MEG) and/or functional magnetic resonance imaging. However, current neuroimaging techniques impose specific requirements on the tactile stimulus delivery equipment in terms of compatibility with the neurophysiological methods being used. Here we present a user-friendly, MEG compatible, tactile virtual reality stimulator and we demonstrate its effectiveness in measuring vibrotactile detection thresholds in active tactile exploration. The stimulator consists of a piezo-electric device capable of independently protruding 16 plastic pistons of 1 mm diameter arranged in a 4 x 4 matrix. The stimulator delivered a spatial pattern of tactile stimuli to the tip of a finger depending on the position of the finger moving across a 2-dimensional plane. The 2-dimensional plane represented various spatial patterns generated in a computer screen. We determined participants’ detection thresholds in active and passive conditions. Results demonstrate ecological validity and threshold estimation efficiency of the virtual reality setup. Due to the compatibility of the stimulator with neuroimaging techniques such as MEG, the apparatus has an immense potential for the exploration of the neural underpinnings of active tactile perception.